PERAN JOYAH DALAM MENINGKATKAN KAPASITAS LANSIA PEREMPUAN DI KABUPATEN ACEH TENGAH - Sari, Rosnida (Universitas Islam Negeri Ar-Raniry, 2019)
This articles shows about the profile of nursing home in Central Aceh District of Aceh Province. In liteal meaning, the meaning of Joyah is a place where women staying together and they do their daily routine such as reciting Al-qur’an and gathering with other nursing home members. However, the function of nursing home in this era is different from the past. This reaseach was made by qualitative method. The data was collected by depth interview with some joyah members and the caretaker of Joyah. Now, the function is just as a nursing home how this women staying together, reciting Holy book and having exercise together and trying their health always fit by having some medical care by health center in town which come once a week. While, in the past the function of Joyah is to promote women leader by having opportunity to teach another women in that area. Eventhough another function is still exist, however the function to create Muslim women leader now is vanish.